METODA PERSAMAAN INTEGRAL BATAS UNTUK MASALAH KONDUKSI PANAS TAK LINIER - Widjaya, Jalina
Abstract: A formulation is proposed to be added into Boundary Element Method, to solve nonlinear heat conduction problems. By this formulation, the solution is expected to be able to reflect the nonlinear characteristics that the original problems have. The formulation consist of : usual boundary element techniques and Direct Regular Method used to locate source point; and some integral formulae to evaluate the coefficients of dicretized boundary integral equations.